Musculoskeletal Imaging: Current Practice and Future Directions - Farrell, Terence Patrick; Adams, Niamh Catherine; Walsh, John P.; Hynes, John; Eustace, Sarah Kate; Kavanagh, Eoin (Seminars in Musculoskeletal Radiology, 2018)
Musculoskeletal (MSK) radiology plays a crucial role in the diagnosis and management of MSK disorders and has rapidly expanded in tandem with advances in technology and improved access to imaging. Although anatomical imaging remains the mainstay of MSK radiology, significant progress has been made in functional and molecular imaging as well as in hybrid imaging with an expanding armament of technologies becoming available or in development. A vast array of research is occurring in MSK imaging, and this review article highlights some of the most promising current and future clinical applications in development in each of the major imaging modalities. Identifying the clinical utility of these technologies in an era of rising health care costs is an important challenge for MSK radiologists.
Keywords: magnetic resonance imaging; computed tomography; ultrasound; hybrid imaging; functional imaging